Comparion of approximations for differential equations - Driss, Sayah; hani, Khezzane (My University, 2022)
هذا العمل مخصص لدراسة و مقارنة التقريبات التحليلية لحلول أنظمة المعادالت التفاضلية أوالً الالخطية من الدرجة الثانية بطرق مختلفة. قدمنا جميع الخصائص والمفاهيم األساسية المستخدمة في دراستنا ، ثم درسنا مبادئ طرق التقريب المختلفة . أخي ًرا ، طبقنا هذه الطرق لحل و مقارنة الحلول التقريبية ألمثلة أساسية وتمثيلها بيانيا ودراسة سلوكها.This work is devoted to the study and comparison of analytical approximations to solutions of systems of nonlinear second order differential equations in different methods. We first introduced all the basic properties and concepts used in our study, and then studied the principles of different approximation methods. Finally, we apply these methods to solve and compare approximate solutions to basic examples, represent them graphically, and study their behaviour.
memoire master mathematique
Keywords: Approximation, Theory of perturbation, periodic solution, simple, avergning , Lindstedt-Poincaré method and renormalization group methods.; التقريب ، نظرية اإلضطراب ، الحلول الدورية، طرق التقريب البسيط والمتوسط و النديست بوانكارييه و طريقة مجموعة إعادة التطبيع.